Verbal and Visual Sign in Selected Cosrx Instagram Ads - Wiryana, Dewa Gede Agus Krisna Putra; Hikmaharyanti, Putu Desi Anggerina (Jurnal Penelitian Mahasiswa Indonesia, 2024)
AbstractThe utilization of both verbal and visual elements plays an important role in ads. This study seeks to discern the verbal and visual cues and also delve into the significance of colors employed in Cosrx advertisements. The research is grounded in the observation method, a means to elicit comprehensive and nuanced insights. In terms of analytical methodology, the study adopts a descriptive qualitative approach. The analysis yielded a dataset comprising 22 instances, subdivided into 8 verbal and 14 visual cues. Within advertisements, a prominent trend is the inclusion of product ingredient names, such as AHA/BHA, Retinol, and Snail. These names function as a form of verbal sign, effectively conveying key information about the products to readers. This tactic assists in enlightening consumers about the specific components featured in the products, thereby heightening their awareness and understanding. Ultimately, the research elucidates how these strategies effectively communicate product attributes and qualities to consumers, fostering a more informed engagement with the advertised products.